Oblicza śmierci człowieka w myśli Sulpicjusza Sewera - Pochwat, Józef (Vox Patrum, 2018)
Sulpicius Severus (c. 360-420) was interested in various cases of human death. Although he do not deny that Christ is the one who alone can save man from death, he does not emphasize this truth either. He is mainly interested in wonders, extraordinary events linked mostly with St. Martin of Tours who was his friend. These miracles performed by Martin had their source in God’s power, but the way they are described places Martin in the centre and presents him as the main character. In this way, Sulpicius brings in a new style of writing, hagiographic literature where though God is the most important, the reader gets the impression that the central figure is a saint. Even though miracles happen by the power of God, one gets the impression that they are the result of the holy man’s efforts and merits. Sulpicius Severus considers death, caused by various ways and experienced for different reasons, is the greatest misfortune of man. He describes many examples related to the phenomenon of death. He talks about the death penalty. Although he mentions death as turning away from God, he does not mean eternal death, but rather its temporal consequences such as deprivation of freedom and falling into a state of slavery.